UPAYA KEPALA SEKOLAH MENGATASI KESULITAN GURU KELAS IV DALAM MENGAJAR PADA KURIKULUM MERDEKA SDN 19 SEBAMBANG TAHUN PELAJARAN 2024/2025 - Sulastri; Arnadi; Parni (CV. ADIBA ASIHA AMIRA, 2026)
This research began from the difficulties teachers face in the teaching process using the independent curriculum. The purpose of this study is to describe: 1) The principal's strategies for overcoming the difficulties faced by fourth-grade teachers in teaching using the independent curriculum, 2) Describing the forms of the principal's efforts to overcome the difficulties of fourth-grade teachers in teaching using the independent curriculum, 3) Describing the results of the principal's efforts in overcoming the difficulties of fourth-grade teachers in teaching using the independent curriculum. This research uses a qualitative approach with a descriptive research type. The data collection techniques in this study used interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The techniques for checking data validity used are source triangulation and member check. The results of this study show that: 1) How the principal's strategy to overcome The difficulties faced by fourth-grade teachers in teaching using the Merdeka curriculum at SD Negeri 19 Sebambang are that the principal conducts supervision, provides facilities and infrastructure, uses a consultative approach and mentorship, and encourages training and workshops. 2) The efforts of the principal to overcome the difficulties faced by fourth-grade teachers in teaching using the Merdeka curriculum at SD Negeri 19 Sebambang are conducting scheduled supervision, organizing internal training and workshops, encouraging teacher collaboration (KKG), facilitating the use and development of learning resources, providing motivation and appreciation, conducting periodic evaluation and monitoring, building positive communication, and encouraging teachers to innovate. 3) The results of the principal's efforts in overcoming teachers' difficulties in teaching using the Merdeka curriculum at SD Negeri 19 Sebambang are increased teacher competence, improved learning quality, the implementation of differentiated learning, and teachers more independent and collaborative, changes in teaching methods, improvement in student learning outcomes, teachers are more professional.